Teacher Management Practices in Institutional Schools of Kathmandu Valley - Shrestha, Rajan Kumar; Aryal, Bhagwan; Khadka, Laxmi (International Research Journal of MMC, 2026)
Effective teacher management is essential for ensuring teachers’ professional competence, ongoing development, job satisfaction, and long-term career stability. It is equally important for the smooth operation and the success of schools. Considering these facts, this study was carried out to find the status of teacher management practices in the institutional schools of the Kathmandu valley with reference to recruitment and selection, participation and empowerment, training and professional development, performance appraisal and reward system, working conditions, and teachers’ facilities. Quantitative research with a survey questionnaire was conducted among 381 teachers of institutional schools of the Kathmandu valley from a total of 4,627 teachers through a multistage sampling method. The data collection was done from July to November 2025 (Shrawan to Kartik 2082 BS). The results yielded from the statistical analyses, one-sample test, and ANOVA, show that the institutional schools of the valley have different teacher management practices. Schools that had leveled up to grade 12 provided better facilities to teachers than other schools (p-value: 0.032). The recruitment and selection practices, as well as the working conditions of Grade-A Schools, were better than those of others. The schools having student numbers 700-900 had better training and professional development practices, performance appraisal and reward system, and teacher facilities than other schools. This study concluded that the institutional schools need to carry out written examinations, including psychological tests of the candidates during the teacher selection process, and should develop a culture of respect for teachers from both parents and students’ sides. In the same way, the school administrators and policy makers need to understand that the facilities provided by institutional schools to teachers are not satisfactory; therefore, they need to improve teachers’ facilities for their motivation and job satisfaction, which in turn increases the educational outcome of the institutions.